Estimating Prevalence and Severity of Caries in the Mixed Dentition: a Comparison of Two Screening Protocols - Susan 0. Griffin, PhD; Paul M. Griffin, PhD; Eugenio D. Beltran-Aguilar, DMD, MS, DrPH, Dolores M. M (Blackwell Synergy, 2004)
Most oral health surveys examine and record data on individual teeth or surfaces (STD), providing valid estimates of caries prevalence and severity.